Effectiveness Of Ethanol Extract Gel Of Leaf Leaves Of Cymbopogon Nardus L) Against Grade Ii A Burn-In White Rats (Rattus Norvegicus) - Nico Marcelino; Ermi Girsang; Ali Napiah Nasution; Chrismis Novalinda Ginting (International Journal of Health and Pharmaceutical (IJHP), 2022)
The writing of the results of this study was carried out to assess the comparison of the effectiveness of the ethanolic extract gel of citronella leaves with concentrations of 5%, 10%, and 15% of each extract on the diameter and thickness of the granulation tissue produced in second-degree burns induced in white rats. This study uses an experimental method with a post-test-only design and the sample is taken using purposive sampling. The effectiveness test was carried out by making IIA degree burns with an iron plate measuring ± 3cm which had been heated and then attached to the skin of rats that had been anesthetized and shaved, after that they were given treatment in the form of applying 5%, 10%, and 10% citronella ethanol extract gel. 15% for each treatment group. The results of the data obtained from this study were continued with the Oneway-Anova test which was continued with the Post-Hoc test, wherein the test results there were significant differences from each treatment given. The results of the measurement of the average diameter of burns resulting from the administration of ethanolic extract gel of citronella leaves given for 21 days with a concentration of 15% showed total healing of burns, while the concentration of 10% showed results of 1.12 cm and 5% of 1.59. cm. From the results of the calculation of the thickness of the granulation tissue, it was found that the administration of ethanol extract gel of citronella leaves with a concentration of 15% was 1074.067 m, a concentration of 10% was 1016,787 m and a 5% concentration was 478.38 m.